Mediterranean Neogene planktonic foraminifer biozonation and biochronology - Lirer F; Foresi LM; Iaccarino SM; Salvatorini G; Turco E; Cosentino C; Sierro FJ; Caruso A (Earth-Science Reviews, 2019)
Planktonic foraminifera are widely used for biostratigraphy and correlation of Mediterranean Neogene marine sediments, and are a fundamental component in the astronomical tuning of the Neogene Time Scale. Recent developments in high-resolution studies, focused on the astronomical calibration of cyclically marine sediments cropping out in land-based sections and recovered from deep-sea successions, increased the accuracy of stratigraphic ranges of planktonic foraminiferal species improving the biostratigraphic resolution and biochronology. The large amount of data on planktonic foraminifera obtained through quantitative/semiquantitative analyses, published in the recent years, allowed the revision of many biohorizons and their calibrations. We incorporate these developments and emendments into the existing Mediterranean planktonic foraminiferal biozonation. Therefore, in this paper, we present an emended Standard Mediterranean planktonic foraminiferal biozonation with a detailed description of zones and subzones within the framework of the Astronomical Tuned Neogene Time Scale 2004 and 2012 (ATNTS2004, ATNTS2012) and we provide the range chart of the most common planktonic foraminiferal taxa and the quantitative distribution pattern of selected marker species. Twenty-two biozones and thirty-one subzones that span the past 23 million years have been identified. We distinguished them using the following code system: MMi1 to MMi13, and NDZ (for the time interval related to the Messinian Salinity Crisis): Mediterranean Miocene biozones, MPl1 to MPl6: Mediterranean Pliocene biozones (according to the Gelasian as the uppermost stage of the Pliocene Series/Epoch), and MPle1 to MPle2: Mediterranean Pleistocene biozones (according to the Calabrian as the lowermost stage of the Pleistocene Series/ Epoch). We assembled 118 Neogene planktonic foraminiferal biohorizons from multiple datasets, and incorporated the calibration of these bioevents into a revised Neogene planktonic foraminiferal biochronology. The revised and ...